Perancangan Sistem Informasi Penjualan dan Pengadaan Barang pada Toko Kartika Jaya - Ayuk Setiatun; Saprudin (OKTAL : Jurnal Ilmu Komputer dan Sains, 2025)
Procurement is an activity process to fulfill or supply the needs and supply of goods or services under a contract or direct purchase to meet the business needs of procurement can affect the entire process of flow of goods because it is a very important part for a company in meeting the company's needs. Based on research that has been conducted at the Kartika Shop, it found tthat the system that the currently applied system had not yet used computerized technology in its daily activity. They still used paper to record every transaction in the store, which often resulted errors due to loss and damage of transaction evidence. Based on this research, the writer tries to make an application to support the activities of the store using the Visual Basic programming language. The method of design is OOAD (Object Oriented Analysis Design) and UML (Unified Modeling Language) is developed as a modeling tool for designing system design. The design was made using Visual Basic and Microsoft Access programming languages as a database. This application is expected to accelerate accessing data of goods, as well as making it easier to report of goods in and out and make reports much better. Moreover, it can help organize stock storage.